Kegiatan Fisioterapi Geriatri pada Lansia dengan Gangguan Kualitas Tidur di Posyandu Puskesmas Mojolangu - Firza Nadia Putri; Rahmat Agung Prakosa; Sri Sunaringsih Ika Wardojo; Eleonora Elsa Sucahyo (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Background: Counseling and counseling is carried out aiming to provide education related to sleep quality disorders in the elderly regarding the causes of sleep disturbances to how to deal with sleep disorders themselves, debriefing is also carried out for the elderly so they can do independent exercises at home to reduce the effects of sleep disturbances experienced Objective: Relieve complaints of sleep disturbances in the elderly and educate about exercises that can be applied independently at home Method: Providing counseling and counseling related to sleep disorders in the elderly using leaflets and asking questions and answers to the elderly and families regarding things that are known about sleep quality. The Pittsburgh Sleep Quality Index (PSQI) questionnaire was also filled out to determine the quality of sleep in the elderly. Results: Counseling and outreach activities can increase the knowledge of both the elderly and their families about the importance of maintaining sleep quality and how to prevent sleep quality. There has been a significant change in which there has been an increase in sleeping hours in the elderly who have sleep disturbances and no longer wake up frequently at night.